Dynamics of Morphological Features of Grass Carp in the Environments of a Fish Hattery in the Bukhara Region - D. B., Usmonova; D. S., Bozorova; M. A. , Yuldashev; M.SH., Shomurotova; B. G., Kamilov (American Journal of Botany and Bioengineering, 2024)
The meristic and plastic features of grass carp (Ctenopharyngodon idella), an important commercial fish introduced to Uzbekistan from China and cultured in new conditions since the 1960s, were determined. The meristic indices were: D III 7, A III 7-8 (8 on average), 39-45 (42) scales in the lateral line, 19-22 (21) rakers on the first gill arch. The indices of plastic features are given according to the classical scheme of measuring carp family fish, as well as by the method of geometric morphometry in grass carp fry and yearlings as important age groups in pond fish farming in Uzbekistan.